The Informed Consent/Assent from the Doctrine of the Mature Minor (2018)
It is necessary to recognize the child as an active moral subject in making decision process related to his health or his participation in research. The taking of informed consent as a communication process should tend to respect the autonomy and dignity of the child considered mature or not, taking their decisions seriously and not just an assent as a normative principle of mere legal aspect. It describes theoretical elements that can be used as tools to have an approach to the moral development of the child from the principle of responsibility according to the degree of emancipation. The objective is to provide a description of the most relevant aspects about the informed consent process in the mature child and their right to be informed to agree or consent. We searched the databases such as: PROQUEST, MEDLINE, LILACS and PUBMED, analyzing 51 articles. For the organization of the information, the SLIDING methodology was used: sort, label, integrate and prioritize. It was concluded that the ability to assent of the child considered mature or not should be evaluated under objective parameters and not simply under the perception of the doctor or researcher. Finally, it is necessary to design strategies to promote the autonomy, respect and dignity of the child based on the same practices at the time of informed consent.